2019
DOI: 10.1097/sla.0000000000003458
|View full text |Cite
|
Sign up to set email alerts
|

Current Epidemiology of Surgical Sepsis

Abstract: Objective: We sought to compare traditional inpatient outcomes to long-term functional outcomes and mortality of surgical intensive care unit (SICU) patients with sepsis. Summary of Background Data: As inpatient sepsis mortality declines, an increasing number of initial sepsis survivors now progress into a state of chronic critical illness (CCI) and their post-discharge outcomes are unclear. Methods: We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 31 publications
6
69
2
Order By: Relevance
“…7). The similarity of CCI to septic shock is not surprising as septic shock is an independent risk factor for the development of CCI [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7). The similarity of CCI to septic shock is not surprising as septic shock is an independent risk factor for the development of CCI [6].…”
Section: Resultsmentioning
confidence: 99%
“…Due in large part to the improvements in sepsis recognition and in subsequent treatment in intensive care units (ICUs), less than 10% of surgical sepsis patients (who can be adequately resuscitated) now die within the first 14 days of their hospital admission [6]. Although over half of surgical sepsis survivors rapidly recover and are discharged from the ICU within 14 days, nearly 50% of them (or ~ 1/3 of all surgical sepsis patients) develop what has been described as chronic critical illness (CCI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in the ICU, GLP-1 level increased 6 times in critically ill patients compared to healthy individuals. It has been concluded that both chronic and acute inflammatory conditions, including sepsis, increase circulating GLP-1 levels (19,20). GLP-1 level tended to decrease in patients who did not develop RH, while it tended to increase in patients who developed RH.…”
Section: Discussionmentioning
confidence: 99%
“…Although acute sepsis treatment has led to more survivors, it has become increasingly apparent that the life-threatening effects of sepsis do not end once a patient leaves the hospital (Fleischmann et al, 2016). In fact, patients have an elevated risk of mortality for at least two years following treatment (Prescott et al, 2016), and more than 20% of survivors will die within a year (Brakenridge et al, 2019). Even healthy individuals who survive sepsis rarely return to normal function (Prescott and Angus, 2018a; Prescott and Costa, 2018b).…”
mentioning
confidence: 99%